European Insecurity: Managing Changing Relations at Home and Abroad - Julie Fraser interviews Dr. M Drent and Dr. B van Ginkel of the Clingendael Institute (Merkourios, 2012)
Interviews with Dr. Margriet Drent and Dr. Bibi van Ginkel of the Security and Conflict Programme of the Netherlands Institute of International Relations 'Clingendael'  Dr. Margriet Drent is a Senior Research Fellow at the Security and Conflict Programme of the Netherlands Institute of International Relations 'Clingendael' and Assistant Professor at the International Relations and International Organisation Department of the University of Groningen. Dr. Drent's PhD on the 'Europeanisation of security' focused on what is now known as the Common Security and Defence Policy. She is also a member of the Peace and Security Committee of the Advisory Council on International Affairs.  Dr. Bibi van Ginkel, LL.M. is a Senior Research Fellow at Security and Conflict Programme of the Netherlands Institute of International Relations 'Clingendael'. She is also a fellow at the International Centre on Counter-Terrorism. Her research concentrates on legal aspects of security issues. She received her doctorate at Utrecht University with a dissertation on the practice of the United Nations on combating terrorism. She is also a member of the Peace and Security Committee of the Advisory Council of International Affairs.